2013
DOI: 10.1155/2013/796715
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabinoid Receptor Type 1 Is Essential for Mesenchymal Stem Cell Survival and Differentiation: Implications for Bone Health

Abstract: Significant loss of bone due to trauma, underlying metabolic disease, or lack of repair due to old age surpasses the body's endogenous bone repair mechanisms. Mesenchymal stem cells (MSCs) are adult stem cells which may represent an ideal cell type for use in cell-based tissue engineered bone regeneration strategies. The body's endocannabinoid system has been identified as a central regulator of bone metabolism. The aim of the study was to elucidate the role of the cannabinoid receptor type 1 in the differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 37 publications
2
45
0
1
Order By: Relevance
“…We have also found that this pro-survival effect of CBD could be mediated by the CB1R. These results are corroborated by other studies which have showing that CB1R activation correlated with reduced apoptosis (Gómez del Pulgar et al, 2000) and increased mesenchymal stem cell survival (Gowran et al, 2013). …”
Section: Discussionsupporting
confidence: 90%
“…We have also found that this pro-survival effect of CBD could be mediated by the CB1R. These results are corroborated by other studies which have showing that CB1R activation correlated with reduced apoptosis (Gómez del Pulgar et al, 2000) and increased mesenchymal stem cell survival (Gowran et al, 2013). …”
Section: Discussionsupporting
confidence: 90%
“…It has previously been reported that CB1 enhances the early osteogenic ability of BMSCs. 22 Meanwhile, the deletion of CB1 causes deossification in mice. 29 Our results are consistent with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lifetime treatment with the CB1‐specific agonist meth‐AEA (an AEA analogue) significantly attenuates the loss of alveolar bone in a rat periodontitis model . Previous studies have found that CB1 is activated during the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) in mice, and CB1 enhances the early osteogenic ability of BMSCs and influences their survival during acute stress . One study has reported that CB1 regulates BMSC migration/homing in mice, and this mediated BMSC function can be enhanced by the CB1‐specific agonists ACEA and weakened by the CB1‐specific antagonist AM281 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, MSCs undergoing osteogenic differentiation have been shown to upregulate CB1 receptors on their surface and activation of CB1 receptors has been reported to positively affect their survival. 43 PEA and DHEA do not mediate their effects via CB1 and CB2. In the central nervous system (CNS), DHEA has been reported to stimulate synaptogenesis and to enhance synaptic connectivity in a CB1-and CB2-independent manner; 44 however, receptors for DHEA still remain to be identified.…”
Section: Discussionmentioning
confidence: 87%